Airway Dysfunction in Obesity: Response to Voluntary Restoration of End Expiratory Lung Volume - Oppenheimer, Beno W.; Berger, Kenneth I.; Segal, Leopoldo N.; Stabile, Alexandra; Coles, Katherine D.; Parikh, Manish; Goldring, Roberta M. (PloS one, 2014)
Abnormality in distal lung function may occur in obesity due to reduction in resting lung volume; however, airway inflammation, vascular congestion and/or concomitant intrinsic airway disease may also be present. The goal of this study is to 1) describe the phenotype of lung function in obese subjects utilizing spirometry, plethysmography and oscillometry; and 2) evaluate residual abnormality when the effect of mass loading is removed by voluntary elevation of end expiratory lung volume (EELV) to predicted FRC. 100 non-smoking obese subjects without cardio-pulmonary disease and with normal airflow on spirometry underwent impulse oscillometry (IOS) at baseline and at the elevated EELV. FRC and ERV were reduced (44 ± 22, 62 ± 14% predicted) with normal RV/TLC (29 ± 9%). IOS demonstrated elevated resistance at 20 Hz (R20, 4.65 ± 1.07 cmH2O/L/s); however, specific conductance was normal (0.14 ± 0.04). Resistance at 5-20 Hz (R5-20, 1.86 ± 1.11 cmH2O/L/s) and reactance at 5 Hz (X5, -2.70 ± 1.44 cmH2O/L/s) were abnormal. During elevation of EELV, IOS abnormalities reversed to or towards normal. Residual abnormality in R5-20 was observed in some subjects despite elevation of EELV (1.16 ± 0.8 cmH2O/L/s). R5-20 responded to bronchodilator at baseline but not during elevation of EELV. This study describes the phenotype of lung dysfunction in obesity as reduction in FRC with airway narrowing, distal respiratory dysfunction and bronchodilator responsiveness. When R5-20 normalized during voluntary inflation, mass loading was considered the predominant mechanism. In contrast, when residual abnormality in R5-20 was demonstrable despite return of EELV to predicted FRC, mechanisms for airway dysfunction in addition to mass loading could be invoked.